Pengaruh Model Pembelajaran Course Review Horay (CRH) terhadap Hasil Belajar PAI Siswa di SMPN 1 Tigo Nagari Kabupaten Pasaman - Inel Inel; Deswalantri Deswalantri (YASIN, 2026)
Low student learning outcomes in Islamic Religious Education and Character Education (PAI BP) remain a concern in various educational studies. Nevertheless, studies that specifically analyze the effect of the Course Review Horay learning model on students’ learning outcomes in the topic of the Role of Muslim Scientists during the Umayyad Dynasty at the junior high school level remain limited. This study aims to analyze the effect of the Course Review Horay learning model on the learning outcomes of seventh-grade students in the PAI BP subject at SMPN 1 Tigo Nagari, Pasaman Regency. This study used a quantitative approach with a quasi-experimental design of the nonequivalent control group design type. The research sample consisted of 60 students selected through purposive sampling, comprising 30 students in the experimental class and 30 students in the control class. Data were collected through learning outcome tests in the form of a pretest and posttest, and were then analyzed using descriptive statistics and a t-test with the assistance of SPSS version 20. The results showed that the mean score of the experimental class increased from 49.90 to 77.47, whereas the mean score of the control class increased from 45.57 to 57.97. The hypothesis test results showed a calculated t-value of 49.533 with a significance value of 0.000 (<0.05), indicating that the Course Review Horay learning model had a significant effect on students’ learning outcomes. These findings strengthen the relevance of cooperative learning and social constructivism, which emphasize students’ active engagement in the learning process. The conclusion of this study confirms that the Course Review Horay model can serve as an alternative innovative learning strategy for PAI BP teachers in improving students’ learning outcomes. The implications of this study encourage the use of more active, participatory, and enjoyable learning models in PAI BP learning, while also opening opportunities for further research with broader samples and coverage of students’ affective and psychomotor aspects.